2021
DOI: 10.1039/d1tb01261d
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic core–shell electrospun scaffolds with sustained release of IONPs facilitating in vitro and in vivo bone regeneration

Abstract: Core–shell electrospun scaffolds with γ-Fe2O3 encapsulation were first fabricated with enhanced physical and mechanical properties, and could promote osteogenic differentiation of rADSCs and in vivo bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The carbon nanotubes positively affected cell adhesion, according to preliminary research conducted with an osteoblastic cell line. In another study, Hu et al [ 176 ] used poly (lactic-co-glycolic acid)/polycaprolactone/beta-tricalcium phosphate (PPT) scaffolds in another study with γ-Fe 2 O 3 encapsulation. The γ-Fe 2 O 3 scaffolds were coated with polyglucose sorbitol carboxymethyl ether.…”
Section: Tissue Engineering Applications Of Fe 2 O...mentioning
confidence: 99%
“…The carbon nanotubes positively affected cell adhesion, according to preliminary research conducted with an osteoblastic cell line. In another study, Hu et al [ 176 ] used poly (lactic-co-glycolic acid)/polycaprolactone/beta-tricalcium phosphate (PPT) scaffolds in another study with γ-Fe 2 O 3 encapsulation. The γ-Fe 2 O 3 scaffolds were coated with polyglucose sorbitol carboxymethyl ether.…”
Section: Tissue Engineering Applications Of Fe 2 O...mentioning
confidence: 99%
“…In vitro biocompatibility studies showed that the incorporation of MNPs was beneficial for the viability, proliferation, and differentiation of WJMSCs. Recent reports indicate that static magnetic fields not only enhance cell viability but also stimulate bone formation in vitro and in vivo [ 55 , 56 ]. From the above results, it can be reasonably inferred that MNPs can be regarded as a single magnetic domain that provides an intrinsic nanoscale magnetic field [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of IONPs is the key factor on cell viability when incubated with cells. Low iron concentration (50 and 100 mg/ml IONPs) had no obvious toxic effect on the proliferation of rADSCs, whereas the cell proliferation ability decreased at 200 mg/ml [ 70 ].…”
Section: Biocompatibilitymentioning
confidence: 99%